Development of the permanent tetrad wall in Juncus L. (Juncaceae, Poales) - Passarini Lopes, Fernanda [UNESP] (2021)
Juncaceae, a cosmopolitan family, belong to the cyperid clade of Poales together with Cyperaceae and Thurniaceae. Pollen grain of Juncaceae, as in Thurniaceae, is dispersed in a permanent tetrad, and knowledge about the ontogeny of its wall is still incipient, based on data from only one species. This study aims to analyze the formation of the pollen wall of seven Juncus species in order to characterize the timing and the ontogenetic events that lead to the cohesion of the four pollen grains in a permanent tetrad. Anthers at different developmental stages were submitted to techniques of light microscopy and transmission electron microscopy; dehiscent anthers with mature pollens were also analyzed in scanning electron microscopy. In all the species here studied, callose deposits around each microsporocyte, with dissolution prior to meiosis. Microspore wall starts at the end of the second meiotic division with formation of primexine. Exine comprises tectum, columellae, and foot layer. During cytokinesis, cell plates form the internal wall of the pollen tetrad. Mature permanent tetrad is enveloped externally by both the exine and intine and internally by the intine and the foot layer, which forms the continuous internal wall. Callose was detected in the early stages of microsporocytes, although reported to be absent in Juncaceae. Our data confirm the variation in Juncaceae cytokinesis and the occurrence of simple cohesion due to the presence of a continuous tectum along the pollen tetrad.